2021
DOI: 10.3390/biom11020240
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Defense against the Pathogenic Fungus Drechslera gigantea Is Dependent on the Integrity of the Unfolded Protein Response

Abstract: Drechslera gigantea Heald & Wolf is a worldwide-spread necrotrophic fungus closely related to the Bipolaris genus, well-known because many member species provoke severe diseases in cereal crops and studied because they produce sesterpenoid phytoxins named ophiobolins which possess interesting biological properties. The unfolded protein response (UPR) is a conserved mechanism protecting eukaryotic cells from the accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER). In plants, consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 76 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…Therefore, on the whole, these results demonstrated that CA targeted plasma membrane where it inhibited PMA, leading to transmembrane potential impairment. To visualize the ER structure, leaves from A. thaliana plants expressing the fluorescent protein GFP-tmKKXX, which specifically localizes in the ER, were used [ 28 ]. Results of confocal microscopy showed that the integrity of the continuous ER network was not significantly affected by 10 or 100 μM CA ( Figure 5 d) Hence, this result indicated that ER is not a primary target of CA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, on the whole, these results demonstrated that CA targeted plasma membrane where it inhibited PMA, leading to transmembrane potential impairment. To visualize the ER structure, leaves from A. thaliana plants expressing the fluorescent protein GFP-tmKKXX, which specifically localizes in the ER, were used [ 28 ]. Results of confocal microscopy showed that the integrity of the continuous ER network was not significantly affected by 10 or 100 μM CA ( Figure 5 d) Hence, this result indicated that ER is not a primary target of CA.…”
Section: Resultsmentioning
confidence: 99%
“…The chlorophyll content of A. thaliana leaves was estimated as described previously [ 28 ]. One hundred mg of control or CA-treated leaves were collected in a Falcon tube with 5 mL of DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations